2004
DOI: 10.1128/aem.70.1.174-181.2004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 2,2′- and 3,3′-Dihydroxybiphenyl by the Biphenyl Catabolic Pathway of Comamonas testosteroni B-356

Abstract: The purpose of this investigation was to examine the capacity of the biphenyl catabolic enzymes of Comamonas testosteroni B-356 to metabolize dihydroxybiphenyls symmetrically substituted on both rings. Data show that 3,3-dihydroxybiphenyl is by far the preferred substrate for strain B-356. However, the dihydrodiol metabolite is very unstable and readily tautomerizes to a dead-end metabolite or is dehydroxylated by elimination of water. The tautomerization route is the most prominent. Thus, a very small fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
(43 reference statements)
1
37
0
Order By: Relevance
“…For example, 3,3Ј-dihydroxybiphenyl is converted to an unstable dihydrodiol metabolite that readily isomerizes to 3,4-dihydroxy-5-(3Ј-hydroxyphenyl)-5-cyclohexen-1-one, which is a dead-end metabolite (18). Several hydroxychlorobiphenyls were also found to generate unstable dihydrodiol metabolites (19).…”
Section: (2 3) the Cis-(2r3s)-dihydroxy-1-phenylcyclohexa-46-dienmentioning
confidence: 99%
“…For example, 3,3Ј-dihydroxybiphenyl is converted to an unstable dihydrodiol metabolite that readily isomerizes to 3,4-dihydroxy-5-(3Ј-hydroxyphenyl)-5-cyclohexen-1-one, which is a dead-end metabolite (18). Several hydroxychlorobiphenyls were also found to generate unstable dihydrodiol metabolites (19).…”
Section: (2 3) the Cis-(2r3s)-dihydroxy-1-phenylcyclohexa-46-dienmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Thus, toluene dioxygenase (TDO) [2,3,[7][8][9][10][11], naphthalene dioxygenase (NDO) [9,12], biphenyl dioxygenase (BPDO) [9,12,13] and o-xylene dioxygenase (OXDO) [14] have all been used to catalyse the formation of catechols B, as major metabolites of phenols A. To date, the binding interactions of phenolic substrates with amino acid residues at the active site of RHDs are relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that, in many cases, catechols B were accompanied by a new family of cyclohex-2-en-1-one cis-diols, as major metabolites (F and G) [7][8][9][10][11]13]. Biotransformations of phenols, with the TDO-expressing constitutive mutant Pseudomonas putida UV4 and recombinant strain Escherichia coli p-CL-4t, resulted in more than twenty cyclohex-2-en-1-one cis-diols (F and G) being added to this new family of metabolites [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathway used by aerobic bacteria to degrade biphenyl is also used to metabolize or cometabolize several hydroxy-and hydroxychlorobiphenyls with an initial attack by the biphenyl dioxygenase (BPDO) (9). However, the profile of the metabolites generated by this pathway has been determined for only a few of these biphenyl analogs (8,10,11). The metabolism of an ortho-hydroxylated biphenyl by a monooxygenase has also been reported.…”
mentioning
confidence: 99%